Rancang Bangun Sistem Informasi Monitoring Perkembangan Proyek Berbasis Web - M Mudjahidin; Nyoman Dita Pahang Putra (Jurnal Teknik Industri, 2010)
Bina Marga and Pematusan official (Bimatus) is government office that deals with transportation improvement and maintenance especially streets and bridges. Each of projects in Bina Marga and Pematusan official has work planning data. Those early data are used as a measure for project development. Consequently, project development information is one of the important things to know whether a project is running well. According to that need along with computer based system improvement that is used to maintenance real and planning data, official would know whether project realization is running well or not. System development is begun with needs identification, then, created system design that is explained with UML and ERD. System design is used in web circumstances, WAP-PHP based, and MySql database. Finally, examinations for many functions are done to evaluate system task. This results a web application and WAP that could manage project development data at Bina Marga and Pematusan Official.